The Theme of the Exodus in Russian Folklore: The “Pharaoh” Mythical Creatures, According to the Archive of the Estonian Literary Museum - Boganeva, Elena; Kõiva, Mare (Studia mythologica Slavica, 2020)
In this article, we will consider the Russian folklore retellings of the Exodus, with special emphasis on the narratives about mythical creatures called “pharaohs”. The current analysis is based on a Russian collection of folklore. The data were collected in the 1920–‘40s in the territories of Estonia, Russia, and Latvia (Lutsi region, Estonian settlement) in the context of Slavic belief systems and legends about these characters. Currently, folklore materials are stored in the archive collection of the Estonian Literary Museum (ELM) (Tartu), and in the Skriptoorium. The article gives an overview of the most characteristic motifs, the origin, appearance, and habitat of these mythical creatures. The actions of the Pharaohs are described in more detail.